Post SARS-CoV-2 multisystem inflammatory syndrome: A clinical case (Archives of Pediatrics of Uruguay, 2022)
In Uruguay, the SARS-CoV-2 pandemic has affected the pediatric population less and the number of positive cases in this age group has increased proportionally to the rise of the virus circulation. The presentation is generally asymptomatic or with mild to moderate respiratory symptoms. Post-Infection Multisystem Inflammatory Syndrome by SARS-CoV-2 (MIS-C) has been described as one of the main post-infection complications.We describe the first case of a patient with MIS-C in the city of Paysandú, Uruguay. It is a 6-year-old schoolboy who had had a SARS-CoV-2 infection a month earlier.He showed a 4-day history of fever associated with skin lesions and conjunctival injection and odynophagia, with high inflammatory parameters and cardiac involvement. He was transferred to a local ICU and had a good subsequent evolution.The high index of suspicion of MIS-C improves the diagnosis and consequently the morbidity and mortality rates of the disease.
Keywords: Coronavirus infections; Systemic inflammatory response syndrome; Mucocutaneous lymphonodular syndrome; COVID-19